POTENSI KEJADIAN IKUTAN PASCA IMUNISASI (KIPI) VAKSIN COVID 19: Analisis Wacana Kritis Model Teun A. Van Dijk Pada Pemberitaan Antaranews.com dan Tribunnnews.com - Ambar Febrianti (2022)
The news of the Covid-19 vaccine AEFI in online news media can cause public unrest, especially those who have not been vaccinated, because the news is a picture of reality constructed by the author. This study aims to interpret the discourse on the potential for Post Immunization Adverse Events (AEFI) after the Covid-19 vaccination. The method used is descriptive qualitative using data sources of 12 news documents consisting of 6 reports on the Antaranews.com and Tribunnews.com sites for the period May to August 2021. The sampling technique was carried out by purposive sampling with a news analysis unit. This study uses a qualitative approach with the method as well as the theory of critical discourse analysis of the Teun A Van Dijk model which includes isis structure, social cognition, and social context. The results of this study indicate that in the news there is media alignment with the government in the discourse built by Antaranews.com and Tribunnews.com. Antaranews.com is ideologically different in presenting the news, using more single sources, namely people who have experienced AEFI after the Covid-19 vaccination and describing the storyline of how it started before the AEFI occurred, while Tribunnews.com prioritizes education by presenting sources who are experts in their fields for more information. explore the phenomena that occur in the news.